Nāṭyaśāstra and the Indian dramatic tradition (Samīkṣikā series, 2012)
Papers presented at the National Seminar on "The Manuscript Tradition of Nāṭyāśastra, Drama and Stage Performance", held at Sagar during 18-20 November 2006